2014
DOI: 10.1039/c3nr04752k
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring surface plasmons of high-density gold nanostar assemblies on metal films for surface-enhanced Raman spectroscopy

Abstract: Plasmonic systems based on metal nanoparticles on a metal film have generated great interest for surface-enhanced Raman spectroscopy (SERS) chemical sensors. In this study, we describe the fabrication of ultrasensitive SERS substrates based on high-density gold nanostar assemblies on silver films with tailored surface plasmons, where multiple field enhancements from particle-film and interparticle plasmon couplings and lightening rod effects of sharp tips of nanostars contribute to the enormous Raman enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 68 publications
2
112
0
Order By: Relevance
“…67 For AuNS assemblies on glass substrates, the field enhancement from AuNS-AuNS coupling has previously been shown to decrease exponentially with increasing interparticle distance, as is typically observed for nearfield interactions in nanoparticle assemblies. 74 In summary, our analysis suggests that tuning the total fluorescent enhancement essentially depends on controlling the excitation enhancement, and illustrates the significant impact of nanotopography on fluorescence enhancement. Our findings clearly demonstrate that AuNS substrates are effective MEF platforms for the enhancement of light from NIR dyes, leading to brightness comparable to that of visible dyes.…”
Section: Fluorophore This Observation Implies That the Electromagnetmentioning
confidence: 99%
See 1 more Smart Citation
“…67 For AuNS assemblies on glass substrates, the field enhancement from AuNS-AuNS coupling has previously been shown to decrease exponentially with increasing interparticle distance, as is typically observed for nearfield interactions in nanoparticle assemblies. 74 In summary, our analysis suggests that tuning the total fluorescent enhancement essentially depends on controlling the excitation enhancement, and illustrates the significant impact of nanotopography on fluorescence enhancement. Our findings clearly demonstrate that AuNS substrates are effective MEF platforms for the enhancement of light from NIR dyes, leading to brightness comparable to that of visible dyes.…”
Section: Fluorophore This Observation Implies That the Electromagnetmentioning
confidence: 99%
“…40 Therefore, control of these morphological features allows systematic tunability of their optical properties across a wide range of the electromagnetic spectrum, reaching the NIR and NIR-II regions. 40,41 As a result of their LSPR, the local electric field near their sharp tips, between the spikes of individual AuNS, or between the spikes of adjacent nanostars, can be enhanced by several orders of magnitude, 40,42 holding great promise for large fluorescence enhancement. Their fabrication by wet chemical synthesis is low cost, readily scalable and can ultimately allow to synthesize multifunctional MEF agents, which induce bright NIR/NIR-II fluorescence and simultaneously carry other diagnostic or therapeutic molecules.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…On these substrates multiple fi eld enhancements from particle-fi lm and interparticle plasmon couplings are expected and lightening rod effected of sharp tips of nanostars contributes to the enormous values of the Raman enhancement that has been described [ 20 ]. The authors showed that the interparticle and particle-fi lm plasmon couplings of high-density GNS on metal and dielectric fi lms can be tuned through the interparticle separation to provide maximum SERS effects.…”
Section: Application Of Gns For Sensing Assaysmentioning
confidence: 94%
“…41 the sensing merits of metallic structures, such as nanostars, 57 nanorings, 58 nanocrosses, 59 nanodisks, 60 and so on. 41 the sensing merits of metallic structures, such as nanostars, 57 nanorings, 58 nanocrosses, 59 nanodisks, 60 and so on.…”
Section: Introductionmentioning
confidence: 99%